Some Aspects in N-dimensional almost Periodic functions III - Arguedas Troyo, Vernor (2004)
The properties of almost periodical functions and some new results have been published in [CA1], [CA2] and [CA3] In this paper we show some new definitions in order to analize some singularities. For this functions we find some uniqueness sets in R and Rn. The paper finishes analizing the relation of this functions and the function sinc.